Corona-Type Textures in Ultrabasic Complexes of the Serpentinite Belt, Kola Peninsula, Russia - Andrei Y. Barkov; Andrey A. Nikiforov; Robert F. Martin; Vladimir N. Korolyuk (Minerals, 2023)
For the first time, corona-type textures are described in ultrabasic rocks in three complexes of the Serpentinite Belt on the Kola Peninsula in the northeastern Fennoscandian Shield. Three variants of the corona texture formed at different stages during the crystallization of a komatiitic, Al-undepleted melt emplaced in a subvolcanic setting. The first type crystallized at an early stage (Mg# Ol = 87) in a fine-grained harzburgite of the Chapesvara-I sill, with the following order in the corona: Ol → Opx → Cpx → Pl → Amp (aluminous sodic-calcic). The second type displays the sequence Opx → Cpx → Amp → Pl → Qz, which is observed in the orthopyroxenite zone in the Lotmvara-I sill. The third type involves a symplectitic corona in a plagioclase-bearing orthopyroxenite in the Lyavaraka complex, in which the inferred order is: Cpx → Amp (aluminous hornblende) + symplectitic Qz, formed in direct contact with grains of Pl. The corona-type textures occur in fresh rocks and are not related to regional metamorphism. They likely formed as consequences of two important factors: (1) rapid cooling, leading to unsteady conditions of crystallization in a shallow setting; and (2) an intrinsic enrichment in H2O and other volatiles in the parental magma, giving rise to fluid-saturated environments at advanced stages of crystallization. This was followed by a deuteric deposition of Amp rims as a result of the accumulation of H2O and reaction of H2O-bearing fluid with early grains of pyroxene and late plagioclase. The likely existence of a close relationship is suggested by the drusites of the Belomorian complex, which are coeval. In addition, unusual occurrences of lamellar inclusions of phlogopite and Al2SiO5 are documented, hosted by interstitial grains of plagioclase in the orthopyroxenite zone of the Lotmvara-I sill. These are attributed to crystallization from late portions of remaining melt enriched in Al, K, Na, H2O, and Cl, which is indicated by the recorded occurrence of chlorapatite in this association. Thus, our findings ...